Odpowiedzi

2010-02-21T16:43:45+01:00
A) -4x - 7 - 3x + 7 =-7x
b) x-2xy + 1/2x - 1/3xy =1,5x-2 1/3xy
c) -x^2 + y^2 - 2x^2 - 2y^2 =-3x^2-y^2
d) -x^2 + 2x - 3x + x^2 =-x
e) 4x + 4 - 7x - 1/2 =-3x+3 1/2
f) -2ab + 12a - 4ab - 16a =-6ab-4a
42 4 42
2010-02-21T16:44:27+01:00
A)-4x - 7 - 3x + 7 = -7x
b) x-2xy + 1/2x - 1/3xy =1 i 1/2x - 2 i 1/3xy
c) -x^2 + y^2 - 2x^2 - 2y^2 = - 3x^2 - y^2
d) -x^2 + 2x - 3x + x^2 =-x
e) 4x + 4 - 7x - 1/2 =- 3x + 3 i 1/2
f) -2ab + 12a - 4ab - 16a =-6ab -4a
32 3 32
2010-02-21T16:45:53+01:00
Musisz laczyc wyrazy podobne:)
to znaczy a z a , b z b, ab z ab, abcdef z abcdef


a) -7x
b) 1,5x - 2 całe i jedna trzecia xy
c) -3x^2 - y^2
d) -x
e) -3x + 3,5
f) -6ab - 4a
121 4 121